2018
DOI: 10.1088/1748-9326/aac4d0
|View full text |Cite
|
Sign up to set email alerts
|

Large scale climate oscillation impacts on temperature, precipitation and land surface phenology in Central Asia

Abstract: Central Asia has been rapidly changing in multiple ways over the past few decades. Increases in temperature and likely decreases in precipitation in Central Asia as the result of global climate change are making one of the most arid regions in the world even more susceptible to large-scale droughts. Global climate oscillations, such as the El Niño-Southern Oscillation, have previously been linked to observed weather patterns in Central Asia. However, until now it has been unclear how the different climate osci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 49 publications
(63 reference statements)
0
42
1
Order By: Relevance
“…Material Fig. S2 and Table S1), and were largely affected by complicated atmospheric circulation patterns (de Beurs and Henebry 2008;de Beurs et al 2018). The SOS trend value in our estimation was about three times the value reported by Garonna et al (2014), more prominent at latitudes over 60°N.…”
Section: Latitudinal Patternsmentioning
confidence: 47%
“…Material Fig. S2 and Table S1), and were largely affected by complicated atmospheric circulation patterns (de Beurs and Henebry 2008;de Beurs et al 2018). The SOS trend value in our estimation was about three times the value reported by Garonna et al (2014), more prominent at latitudes over 60°N.…”
Section: Latitudinal Patternsmentioning
confidence: 47%
“…Seasonal changes in river water temperature shaped by correlations between positive and negative phases of macroscale atmospheric circulation are presented in only a small number of articles. The significance of this problem for research into relations between macroscale types of atmospheric circulation and climatic and hydrological factors has been duly recognized-among others by de Beurs et al [28]. Its crucial importance is underscored by the fact that these changes are critical for maintaining the ecological function of rivers.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that, in the case of rivers in the Northern Hemisphere, we may observe a seasonal distribution of water temperature, while exceptions to this rule may be the result of weather anomalies or of the impact of anthropogenic factors [2,4,12,19]. High correlations between annual and monthly air and river water temperature values have been demonstrated for various regions, among others in the United States and Canada [16,[20][21][22][23][24], in Asia and Eurasia [25][26][27][28], and in Europe [29][30][31][32][33][34][35][36]. Studies concerning the thermal regime of Polish rivers have also confirmed the existence of significant relations and the impact of air temperature on the variability of river water temperature [4,5,13,[37][38][39].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pinatubo eruption. Immediate, short-term impacts of sociopolitical change on rangeland dynamics during this transitional period in this region (figure 3) may therefore have been masked by Mt Pinatubo-induced climate disruption whereas over the longer-term, environmental factors were the primary drivers in NDVI dynamics in the region, Yu et al 2003, Julien et al 2006, Propastin et al 2008, Lioubimtseva and Henebry 2009, Kariyeva and Van Leeuwen 2011, Pinzon and Tucker 2014, Dubovyk et al 2016, de Beurs et al 2018.…”
mentioning
confidence: 99%